Positioning System of Working Bodies in Differential Spraying of Plants - M. A. Mirzaev; I. G. Smirnov (Сельскохозяйственные машины и технологии, 2024)
The paper highlights that the escalation in the use of pesticides and agrochemicals poses a significant risk to human health, environmental integrity, and food safety. The predominant method of pesticide application is crop spraying. Improved eﬃciency and quality of spraying, coupled with a reduction in drug costs, can be achieved by transitioning to diﬀerential treatment of agricultural land and precision dose regulation. The incorporation of robotic devices oﬀers a promising solution to facilitate the process of plant protection. (Research purpose) The research aims to develop a positioning system for a robotic diﬀerential spraying device. (Materials and methods) were subjected to chemical treatment by an autonomous field robot, and the quality of spraying was assessed using a nozzle. (Results and discussion) The research established a relationship between calculating the nozzle capture angle of an individual plant and the angle of lever lift. Subsequently, a computerized spraying model was developed, enabling the adjustment of various parameters and benchmarking the proposed diﬀerential spraying method against the traditional one. The variation coeﬃcient, reflecting the uniformity of droplet distribution on the plant surface, was calculated. The results indicate that the variation coeﬃcient is dependent on the speed and distance of spraying in diﬀerent operating modes, including individual plant spraying and row spraying. (Conclusions) The variation coeﬃcient for the traditional spray method was 46 percent. With the adoption of diﬀerential spraying methods, this variation coeﬃcient decreased to 25-28 percent for individual plant spraying and 33-40 percent for row spraying. Field studies further demonstrated a variation coeﬃcient of 19-24 percent for individual plant spraying in contrast to 30-35 percent for row-spray treatments.